Youth Capacity Strengthening Through Education about Tuberculosis Prevention - Lisum, Kristina; Lestari, Theresia Budi; Anggitafani, Marsella (Universitas Ibn Khaldun, 2024)
Indonesia ranks scond among countries with a high burden of Tuberculosis after India, and there were an increasing burden if youth did not acknowledge about how to prevent the transmission of TBC, especially in the family. The education program was delivered to 25 high school students at SMKN 14, Center of Jakarta. The result of this program that there were an increasing knowldege of 67.5 % students. The student’s knowldege that increased could be forwarded into the family; therefore will increase the family health behavior.